The Community Diagnosis of Filariasis Endemic Villages in Pekalongan City - Siwiendrayanti, Arum; Pawenang, Eram Tunggul; Indarjo, Sofwan (KEMAS: Jurnal Kesehatan Masyarakat, 2016)
The percentages of referrals for the first level health facilities visits are coming from Filariasis cases have increased to 11,699 until 2008. In Pekalongan City, there are 117 infected people in 2011. This study aims at investigating social determinants of filariasis endemic communities in several villages. Surveys using a cross-sectional study design, Population studies that tested positive for finger blood survey (FBS) in 2011-2013. Samples were collected by convenience sampling method sequentially through questionnaires and observation. There were 402 people participating in this study. The result shows that the presence of bushes, puddle, Sewerage are in unfavorable conditions and people do not use mosquito net during sleep and hang clothes. The best prevention practice in Padukuhan Kraton Village is by regularly use mosquito repellent and do not go out at night, Padukuhan Kraton endemic filariasis with mf-rate of 3.7%. Filariasis Elimination Program Year 2011-2015 is carried out properly and in accordance with the regulations of filariasis filariasis Mass Drug Administration (MDA) program. FBS is implemented before MDA (Mass Drug Administration) and handling of cases of chronic filariasis. Respondents have a good knowledge of prevention of transmission of filariasis. Hoewever, the practice of taking the MDA medication is still less. Suggestions for the community are to improve environmental sanitation, improvement of MDA medication and the prevention of transmission of filariasis.